A development of mobile-based directory for UCSI University (UCSI Mobiletory) - Jing, L.C.; Shibghatullah, A.S.; Ling, C.T.C. (International Journal of Human and Technology Interaction (IJHaTI), 2019)
A directory can be known as the board of the organization or locations of certain departments, or certain shop in the context of a shopping mall (Hendriana, Pranolo, Sulaiman, & Fong, 2015). It is important to serves as a guide to people as it can provide locations and information of a mall, especially in the case of a large shopping mall, it is hard to find the directory board (Hendriana, et al., 2015). As the capital of Malaysia, Kuala Lumpur has been constructing many large-scale mall around the city, namely Sunway Pyramid mall, Pavillion mall. Without the implementation of a directory board, people could be lost or taking a lot of times in finding their preferred shop. In the modern society, most of the commerce, business, education and activities are conducted in indoor area. The space needed for these facilities are growing into bigger and buildings are becoming more complex, this has urge the need of localization and mapping services within the buildings. In fact, getting lost in indoors are just as common as getting lost at outdoors. In spite of current outdoor mapping services such as Waze and Google Map that are using satellite technology, a GPS (Global Positioning System) to locate a GPS receiver at the Earth, it cannot provide the same services in indoors. The application was designed to let users search and aware of the information provided to a particular location or facility apart from providing floor plan to them. The methodology used in the system development process is prototyping methodology. The languages involves in the development includes JAVA, PHP and SQL programming language.